2013
DOI: 10.1111/jeb.12196
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effects of recombination and possible nonrecombinatorial advantages of sex in a fungal model

Abstract: Why sexual reproduction is so prevalent in nature remains a major question in evolutionary biology. Most of the proposed advantages of sex rely on the benefits obtained from recombination. However, it is still unclear whether the conditions under which these recombinatorial benefits would be sufficient to maintain sex in the short term are met in nature. Our study addresses a largely overlooked hypothesis, proposing that sex could be maintained in the short term by advantages due to functions linked with sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Lichens often spread asexually by symbiotic propagules (isidia or soredia). In the course of mitotic divisions due to growth or the production of asexual spores, spontaneous mutations are expected to appear regularly (López‐Villavicencio et al, 2013). Dal Grande et al (2012) found that 15% of the fungal genetic diversity detected in 62 populations of L. pulmonaria is generated by somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Lichens often spread asexually by symbiotic propagules (isidia or soredia). In the course of mitotic divisions due to growth or the production of asexual spores, spontaneous mutations are expected to appear regularly (López‐Villavicencio et al, 2013). Dal Grande et al (2012) found that 15% of the fungal genetic diversity detected in 62 populations of L. pulmonaria is generated by somatic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…This zygote multiplies through a series of mitoses, after which each zygote goes through meiosis. This results in sexual fruiting bodies containing up to 10 6 sexual spores (ascospores) representing all possible recombinants of meiosis [29,50,51]. Among the progeny, we expect two parental and two recombinant classes (i.e.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, given that same-clone mating incurs costs of sex without some of the major benefits of recombination, heterothallism may be favoured by selection for increasing the chance to produce recombinant offspring when there is limited haploid dispersal (15, 79). Nevertheless, same-clone mating may allow benefit from indirect advantages of the sexual cycle without breaking apart beneficial allelic combinations (180, 181). Such advantages include the production of resistant sexual spores as a life history constraint, changes in ploidy level and physiology, virus elimination, and genome defenses that depend upon the sexual cycle, such as repeat-induced point mutation (182) or meiotic silencing of unpaired DNA(183).…”
Section: Breeding Systems In the Basidiomycotamentioning
confidence: 99%